2010
DOI: 10.1002/ange.201005100
|View full text |Cite
|
Sign up to set email alerts
|

A Labile and Catalytically Active Imidazol‐2‐yl Fragment System

Abstract: N-heterocyclic carbenes (NHCs) [1] and their complexes [2] are excellent catalysts for a broad array of organic transformations, where the NHC ligands impart useful electronic and steric properties to metal centers. [3] In these systems, with commonly used ancilliary NHC ligands that are substituted at nitrogen atom(s) by alkyl, aryl, or other groups, [2,3] all catalytic transformations take place at the metal center, which is stabilized and/or activated by the NHC ligand. However, transformations that may pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Compared with the C carbene resonance found for the related platinum complex of type trans‐ II (Scheme ) containing the NMe,NH‐NHC ligand ( δ =166.9 ppm in CDCl 3 /[D 6 ]DMSO;11a δ =157.8 ppm in CD 2 Cl 2 , see the Supporting Information), the C carbene resonance for 1 in CD 2 Cl 2 is shifted highfield by Δ δ =8.4 ppm compared with the protonated complex, an effect obviously caused by the anionic character of the benzimidazol‐2‐yl ligand of 1 . A similar highfield shift for the C carbene resonance was observed upon N ‐deprotonation of NR,NH‐NHC ligands coordinated to Ru II (NR,NH‐NHC δ =167.7, NR,N‐NHC 156.4 ppm)12e or Ir I (NR,NH‐NHC δ =140.3, NR,N‐NHC 131.3 ppm) 12b. The C carbene resonance in 2 was detected as a doublet of doublets at δ =157.9 ppm (dd, 2 J CP =8.8 Hz, 3 J CP =2.1 Hz), and this value is in accord with the chemical shift recorded for the C carbene atom in the dinuclear platinum complex III ( δ =159.8 ppm, dd, 2 J CP =8.8 Hz, Scheme ) 11a.…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Compared with the C carbene resonance found for the related platinum complex of type trans‐ II (Scheme ) containing the NMe,NH‐NHC ligand ( δ =166.9 ppm in CDCl 3 /[D 6 ]DMSO;11a δ =157.8 ppm in CD 2 Cl 2 , see the Supporting Information), the C carbene resonance for 1 in CD 2 Cl 2 is shifted highfield by Δ δ =8.4 ppm compared with the protonated complex, an effect obviously caused by the anionic character of the benzimidazol‐2‐yl ligand of 1 . A similar highfield shift for the C carbene resonance was observed upon N ‐deprotonation of NR,NH‐NHC ligands coordinated to Ru II (NR,NH‐NHC δ =167.7, NR,N‐NHC 156.4 ppm)12e or Ir I (NR,NH‐NHC δ =140.3, NR,N‐NHC 131.3 ppm) 12b. The C carbene resonance in 2 was detected as a doublet of doublets at δ =157.9 ppm (dd, 2 J CP =8.8 Hz, 3 J CP =2.1 Hz), and this value is in accord with the chemical shift recorded for the C carbene atom in the dinuclear platinum complex III ( δ =159.8 ppm, dd, 2 J CP =8.8 Hz, Scheme ) 11a.…”
Section: Methodssupporting
confidence: 62%
“…Complexes of type D are extremely rare and have so far only been obtained by deprotonation of coordinated NR,NH‐NHCs 12b. e The direct access to complexes featuring NR,N‐NHC ligands by the oxidative addition of the C2Cl bond of a 2‐halogenato‐benzimidazole is much more facile and allows a rich follow‐up chemistry, such as the N ‐protonation or N ‐alkylation of the NR,N‐NHC ligand. Particularly complexes containing “protic” NHC ligands can be obtained easily this way and these have recently attracted interest as bifunctional catalysts 14…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, Grotjahn found that Ru complex 116 , ligated by a protic N‐heterocyclic carbene–phosphine ligand, was active for transfer hydrogenation of acetophenone (Scheme ) 72. Although the NH moiety does not coordinate directly with the ruthenium center as in the Ru(phosphine) 2 –diamine system, a similar bifunctional mechanism was proposed for the transfer hydrogenation of ketones catalyzed by 116 .…”
Section: Mnh Catalysismentioning
confidence: 98%